2018
DOI: 10.5430/ijhe.v7n5p20
|View full text |Cite
|
Sign up to set email alerts
|

English Language and Literature Students’ Perceptions of Critical Thinking

Abstract: The fundamental purpose of the function of thinking is to attribute meaning to events in our lives, classify these events into categories and identify them subjectively. As an important dimension of education on thinking, the teaching of critical thinking since the 1950s has attained a wide conceptual framework. Accepted as a factor that facilitates the aquisition and comprehension of information, critical thinking is a desirable learning outcome of education.  Some of the characteristics and properties of cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…It can be admitted this study tends to follow most research that found students had a good perception in their use of critical thinking skills in their presentation. To use critical thinking skills, not only use perseverance and patience (Tosuncuoglu, 2018), students need to prepare several important things to use their critical thinking skills.…”
Section: Students' Learning Stylesmentioning
confidence: 99%
“…It can be admitted this study tends to follow most research that found students had a good perception in their use of critical thinking skills in their presentation. To use critical thinking skills, not only use perseverance and patience (Tosuncuoglu, 2018), students need to prepare several important things to use their critical thinking skills.…”
Section: Students' Learning Stylesmentioning
confidence: 99%
“…To illustrate, gender was one of the background variables used in the studies we reviewed. Our analysis showed that while gender was a significant determinant of CTD of pre-service in some of the studies (2,7,12,13,21,23,25,31,35,40,51,62,63,65,74,79,84,85,88), more studies did not find any significant difference between gender and CTD scores of the participants (1,5,10,11,15,19,22,24,27,30,32,37,39,41,45,46,47,50,53,54,55,58,69,71,72,76,77,78,81,86). In addition, almost two-thirds of th...…”
Section: Independent and Background Variables Used In The Reviewed St...mentioning
confidence: 94%
“…CT as a Higher-Order Thinking Process. The review results indicated that CT was specified as a higher-order thinking process in almost half of the studies (n=37) (9,11,12,14,17,21,23,24,25,26,27,28,29,31,32,35,36,38,41,45,50,51,52,55,56,60,69,70,71,72,74,76,77,84,85,87,88). For instance, in study 14, the CT definition of Facione et al (1994) was adopted: "higher-order reasoning used in reaching professionally informed judgments in high-stakes, time-constrained, and many times, novel problem situations" (p. 41).…”
Section: Traditional Perspectivesmentioning
confidence: 99%
“…individuals who can effectively utilize critical thinking in their lives are individuals who possess the skills and disposition necessary for critical thinking. critical thinking is an important cognitive skill that affects students' viewpoints on events, their perceptions concerning what transpires in their environment and their decision-making processes (Tosuncuoglu, 2018). It means that critical thinking is needed as a thinking framework in responding to any issues or problems.…”
Section: Horneymentioning
confidence: 99%